TELAAH KEMAMPUAN SISWA MENENTUKAN UNSUR-UNSUR PARAGRAF DALAM TEKS BACAAN PADA SISWA KELAS IV SDN SEMANAN 04 PAGI - Berliana, Febiani Wangsa; Sundari, Nenden; Suzanti, Lizza (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Understanding the content of reading text in elementary school can be helped by determining the element of paragraph. This study aims to determine of fourth grades at SDN Semanan 04 Pagi in determining the paragraph elements in the reading text. This study uses a qualitative approach using a qualitative descriptive method. The research subjects in this study were 21 students in grade IV. The research instrument used was in the form of tests and interviews conducted on students. This study obtained analysis results which stated that students' ability to determine paragraph elements in reading texts was quite good because on average students were able to find 3-4 paragraph elements correctly. The students’ ability in finding main sentences, explanatory sentences, and affirmative sentences on tests 1, 2, and 3 showed a fairly good ability, while students’ abilities in determining transitions on tests 1, 2, and 3 showed poor abilities. The factors that cause students’ difficulties in determining the elements of paragraphs are lack of understanding of the material, lazy to study, lack of interest and motivation in student learning, no self-motivation to learn, and lack of practice in understanding the meaning of reading texts